2022
DOI: 10.3168/jds.2021-21386
|View full text |Cite
|
Sign up to set email alerts
|

Cattle farmer psychosocial profiles and their association with control strategies for bovine viral diarrhea

Abstract: Bovine viral diarrhea (BVD) is endemic in the United Kingdom and causes major economic losses. Control is largely voluntary for individual farmers and is likely to be influenced by psychosocial factors, such as altruism, trust, and psychological proximity (feeling close) to relevant "others," such as farmers, veterinarians, the government, and their cows. These psychosocial factors (factors with both psychological and social aspects) are important determinants of how people make decisions related to their own … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 69 publications
0
22
0
Order By: Relevance
“…This behaviour is consistent with the behavioural label of parasitism 18 , waiting to see what happens to others rst and expecting to be protected by other farmers vaccinating their herds, only vaccinating if it becomes necessary. Other research has identi ed that high trust in farmers to control disease can reduce the disease prevention behaviours farmers use in their own herd because they perceive their risk of disease from other farms to be low 24,50 , therefore this can be a barrier in disease control. Veterinary advice is generally trusted by farmers 25,27 and this could be a route to promoting interventions to achieve prompt uptake and better epidemic control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This behaviour is consistent with the behavioural label of parasitism 18 , waiting to see what happens to others rst and expecting to be protected by other farmers vaccinating their herds, only vaccinating if it becomes necessary. Other research has identi ed that high trust in farmers to control disease can reduce the disease prevention behaviours farmers use in their own herd because they perceive their risk of disease from other farms to be low 24,50 , therefore this can be a barrier in disease control. Veterinary advice is generally trusted by farmers 25,27 and this could be a route to promoting interventions to achieve prompt uptake and better epidemic control.…”
Section: Discussionmentioning
confidence: 99%
“…Psychological proximity has implications for human health behaviour [29][30][31] but to date has received little investigation in farmer behaviour for controlling livestock disease. Farmers with high psychological proximity to their veterinarian are more likely to control bovine viral diarrhoea in their herd 24 . Behaviour is also in uenced by capability, opportunity and motivation which are theorised in the COM-B behaviour change framework 32 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, dependent upon the disease that is circulating, an individual farmer may accept the risk of infection rather than proactively cull their livestock; yet culling may be a powerful tool to prevent large-scale outbreaks of some diseases. Elicitation of cattle farmer psychosocial beliefs have identified multiple factors as having an association with proactive undertaking of control measures, which include the importance of veterinarians as a source of information, a lack of trust in other farmers, the individual experiences of farmers, and the knowledge and understanding of how and why to control disease and availability of time and money to enact the control [ 8 , 9 ]. To formulate livestock disease intervention policies that will be highly adhered to by all stakeholders, there is a need to quantify, predict and hence mitigate these inevitable tensions between local (farmer-led) and global (regionally- and nationally-enforced) perspectives of control.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the association between farmer behavior and BVDV control at farm level could help reduce the risk of introduction or persistent infections with BVDV. It has been found that the engagement of farmers in BVDV control is important for successful eradication or maintaining freedom at the national level (Prosser et al, 2022;Evans et al, 2018). Farmers psychosocial factors were shown to be linked to BVDV control strategies e.g.…”
Section: Importance Of Herd-level Risk Factorsmentioning
confidence: 99%
“…Farmers psychosocial factors were shown to be linked to BVDV control strategies e.g. farmers that did not trust other farmers were more likely to have a closed herd, farmers with a good connection with their veterinarian were more likely to adopt BVDV control measures (Prosser et al, 2022). In the STOC free framework such factors could be included as risk factors.…”
Section: Importance Of Herd-level Risk Factorsmentioning
confidence: 99%